Implementation of a data acquisition system for contactless conductivity imaging. - Ulker, B. (IEEE Engineering in medicine and biology magazine)
A data acquisition system is realized for conductivity imaging via contactless measurements. It is observed that field profiles are good representatives of the conductive objects scanned by the measurement system. Three different data sets are taken with different scanning resolutions. Note that although the scanning resolution is decreased 25 times, it is still possible to observe the conductive object. The data acquisition time is due to the data acquisition time limit of the lock-in amplifier. As might be expected, the secondary voltage profiles spreads. It is possible to employ an image reconstruction algorithm and obtain conductivity images with better resolution. In conclusion, the first results of a promising new medical imaging modality were presented. This system can provide necessary conductivity information for electromagnetic source imaging of the human brain. Moreover, this system can be applicable to brain, breast and lung imaging. Other application areas should further be explored